Faktor Penyebab Gerakan Tanah di Desa Noelmina Kecamatan Takari, Kabupaten Kupang, Provinsi Nusa Tenggara Timur - Lindung Freedom Boimau; Hendy Setiawan; Wahyu Wilopo (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2026)
A landslide is a process where the mass of rock or soil that forms a slope moves due to the force of gravity in a weak area. Landslides that occurred in Noelmina Village, Takari District, Kupang Regency on February 17, 2023, resulted in the main road, which connects the provincial capital of East Nusa Tenggara and several districts on Timor Island, being completely damaged. This research aims to identify the factors that contribute to landslides in Noelmina Village. This research began with collecting regional geological data, a regional geological structure, then continued with primary data collection in the field for geological mapping, geomorphological, and land use data, while rainfall data was taken from the CHIRPS satellite data. Results indicated that the landslide occurred within the Bobonaro carbonate mudstone unit, characterized by a rather steep slope where the geological structure consisted of joints in the rock mass. Additionally, the landslide was situated in an area influenced by the regional geological structure, specifically the left-hand horizontal fault. The land use conditions of the research area are quite varied, but the areas that experienced landslides were located in forest land uses that directly border residential areas and roads. The rainfall conditions during the landslide in February 2023 had a high intensity of 431mm - 463mm. An XRD analysis was conducted on rock or soil samples from the landslide area, and it was found that expansive minerals, namely montmorillonite, illite, and kaolinite, were present. The results of this research indicate that landslide events in the research area were significantly influenced by factors such as rock/soil conditions, geomorphology, geological structure, land use conditions, and the presence of expansive clay minerals. Furthermore, the dominant factor triggering the landslide was the high-intensity rainfall that took place in the study area of less than one month.